The Complement System: An Important New Therapeutic Target in IgA Nephropathy - Karshana J. Kalyanaraman; Joshua M. Thurman (Glomerular Diseases)
Background: IgA nephropathy is the most common primary glomerular disease worldwide, and it is an important cause of end-stage kidney disease. Until recently, there were not any treatments of proven benefit, and care of patients with IgAN primarily involved supportive measures. Within the past few years, however, multiple new drugs have shown promise in clinical trials. Summary: Among the new drugs, several complement inhibitory drugs have demonstrated efficacy at reducing proteinuria, and there is a strong rationale for expecting that these agents will be effective at slowing progression of the disease. Furthermore, anticomplement drugs target a part of the immune system that is not directly blocked by other classes of immunosuppressive agents. One of the new drugs, iptacopan, is a selective inhibitor of the alternative pathway. Preliminary results from a phase 3 study of iptacopan in IgA nephropathy demonstrated that treatment is associated with a rapid reduction in proteinuria, and the drug recently received accelerated approval from the Food and Drug Administration. Additional drugs that have been tested in IgA nephropathy include agents that block the complement cascade at the levels of C3 and C5. Complement activation in the kidneys of IgA nephropathy patients generates biomarkers that can be detected in the blood, urine, and kidney biopsies. If multiple complement inhibitory drugs receive approval for IgA nephropathy, these biomarkers may be useful for selecting the most appropriate drug for an individual patient. Complement biomarkers may also be useful for monitoring a patient’s response to treatment. Key Messages: Several complement inhibitors are currently in clinical trials for IgAN. Iptacopan recently received accelerated approval for the indication and complement inhibitory drugs will likely become an integral part of the treatment for this disease in the near future. As these drugs become available in the clinic, it will be important to develop biomarkers that can guide clinicians to the best drug for an individual patient.